“PENGARUH LDR, NPM, CAR DAN UKURAN PERUSAHAAN PADA PROFITABILITAS BANK UMUM SWASTA NASIONAL DEVISA 2014-2017 - Felix Ananta Santoso, 14.05.52.0072; Masdjojo, Gregorius N (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the effect of Loan to Deposit Ratio, Net Profit Margin, Capital Adequancy Ratio and Company Size on the Profitability of National Private foreign exchange Banks 2014-2017. This study uses purposive sampling method in sample selection, with sample criteria being companies registered in Indonesia Stock Exchange during the 2014-2017 period. Based on these criteria, a sample of 15 banks was obtained with a period of four years of observation. Because the type of research data is a combination of "Cross-section" and "Time-series" data, the data analysis uses panel data regression analysis method. The estimation process uses the Fixed Effect Model (FEM) and Random Effect Model (REM) methods. Selection of the best model using the "Haussman Test". The results of the data analysis based on the Hausman Test are recommended to use the FEM method, the average of the Bank's Profitability, the bank with the highest average profitability during the period 2014 - 2017 is PT. Bank MNC International, while banks with the lowest average bank profitabilityPT. Bank Nusantara Parahyangan. The results showed that the Loan to Deposit Ratio had a significant positive effect on the Bank's Profitability, Net Profit Margin had a significant positive effect on Bank Profitability, Capital Adequacy Ratio had no significant positive effect on Bank Profitability, Company Size had a significant negative effect on Bank Profitability. Keyword : Bank Profitability (ROA), Loan to Deposit Ratio (LDR), Net Profit Margin (NPM), Capital Adequancy Ratio (CAR) and Company Size (SIZE)..